The Impact of Design Characteristics on the Psychological Connection Between the Heritage Building and its Occupants - Ahmed, Zahraa; Al Ali , Saba Sami (Al-Nahrain Journal for Engineering Sciences, 2024)
Heritage buildings are part of the connection between the past and the present. By paying attention to their occupancy, we keep the present and future generations in touch with what our ancestors achieved, hence sustaining them being part of the living heritage. Restoration and renovation procedures must be carried out to make them capable of meeting contemporary needs, However, it is essential to recognize the architectural characteristics that resonate with long term occupants. This research focuses on the effect of design characteristics on the psychological relationship between heritage buildings and their occupants, through case studies of two heritage buildings in Baghdad. The first is the previous Theological college building of Al al-Bayt University of the 1920s, now the College of education for girls, and the second is the 19th century Ottoman Al-Qishla building. The study relies on conducting a questionnaire for the occupants about their response to design characteristics of each building. The questionnaire concluded that the design characteristics of the heritage building have a significant impact on the psychological response of its occupants. The majority of respondents indicated that characteristics such as clarity of function, clarity of elements, sense of security, privacy, and flexibility, were satisfactory. The majority of respondents expressed appreciation for heritage buildings, as well as positive evaluations and appreciation for the reflection of the past in these buildings, indicating that “architectural characteristics of the heritage building” has a significant impact on the psychological connection felt by the occupants of the heritage building.